Bleeding Risk in Patients Using Oral Anticoagulants Undergoing Surgical Procedures in Dentistry: A Systematic Review and Meta-Analysis - Andrade, Natália Karol de; Motta, Rogério Heládio Lopes; Bergamaschi, Cristiane de Cássia; Oliveira, Luciana Butini; Guimarães, Caio Chaves; Araújo, Jimmy de Oliveira; Lopes, Luciane Cruz (Frontiers in Pharmacology, 2019)
The management of patients who undergo dental surgical procedures and take oral anticoagulants therapy requires special attention due to the risk of bleeding that may or may not occur during the procedure. Bleeding rates in these trans or postoperative patients are uncertain. The aim of this study was to conduct a systematic review in order to assess the risk of bleeding during and after performing oral surgical procedures in patients in use of oral anticoagulants compared to group that discontinued anticoagulant therapy. Cochrane Central Register of Controlled Trials (CENTRAL), MEDLINE (via Ovid), EMBASE (via Ovid) databases and Virtual Health Library (VHL) from the inception of the database to December 2018 were searched. The primary outcome was the occurrence of local bleeding rate during and after oral surgical procedures. Four reviewers, independent and in pairs, screened titles and abstracts for full-text eligibility. Data regarding participant characteristics, interventions, and design and outcomes of included studies were extracted. The data were pooled using random-effects meta-analyses and described as risk ratio (RR) with the 95% confidence interval (95% CI). The confidence on the pooled estimates was ascertained through the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) approach. The protocol of this review was recorded in the PROSPERO (CRD42017056986). A total of 58 studies were identified of which three RCT were included in the meta-analysis, with a total of 323 adults participants and 167 were taking anticoagulant during the dentistry procedure. Of these patients, 14.2% had reported bleeding. The risk of bleed was one to almost three times greater in patients taking warfarin compared to patients who discontinued the use of anticoagulant in the trans operative period (RR= 1.67, 95% CI= 0.97 to 2.89) and in the postoperative period (RR= 1.44, 95% CI= 0.71 to 2.92), with the quality of evidence very low. The findings of this review have demonstrated no evidence in keep out the risk of bleeding when the use of oral anticoagulants is maintained during oral surgical procedures.